DETERMINANTS OF THE TIMELINESS OF PUBLISHING FINANCIAL REPORTS: NON-FINANCIAL COMPANIES IN INDONESIA - Tanujaya, Kennardi; Elliany, Elliany (Universitas Bunda Mulia, 2024)
Background: The timeliness of publishing financial reports is very important for companies and users of financial information. Delays in publishing financial reports can impose sanctions on the company concerned, hinder economic decisions, and even create a bad reputation for the company among investors.Purpose: This research aims to examine the influence of company size, profitability, leverage, number of subsidiaries, board independence, board ownership, audit quality, and composite corporate governance index (CG-Index) on the timeliness of publishing financial reports.Research method: The data analysis method used in this research is panel regression analysis with a total of 439 company analysis units over 5 years.Research result: Panel regression test results show that the variables profitability and board independence have a significant negative effect on the timeliness of publishing financial reports. Audit quality and the CG-Index have a significant positive relationship with the timeliness of publishing financial reports.Originality/Novelty: The research uses the CG-Index to measure the effectiveness of corporate governance in reducing the potential for audit delays in developing countries.